Mengatasi masalah sanitasi lingkungan melalui penerapan desain bak penampungan air kotor dan air hujan sebagai sarana konservasi air - Faizal Amir; Rahmansah Rahmansah; Alimuddin Sa’ban Miru (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The Community Partnership Program (PKM) aims to overcome the problems of the community's environment,especially their environmental sanitation which is also a means of water consolidation. PKM location is in Rompegading Village,Liliriaja District, Soppeng Regency. The PKM partner is the Head of Rompegading Village (Sakmawati, S.S, M.M) representingthe community who have various kinds of environmental problems. Partner problems: (1) partners do not have knowledge aboutthe materials and tools used to make dirty and rain water reservoirs, control tanks, and infiltration tanks; (2) partners do not haveknowledge about the functions of dirty and rain water reservoirs, control tanks, and infiltration tanks; (3) partners do not have theskills to make dirty and rain water storage tanks, control tanks, and absorbing tanks. The solutions offered to solve partnerproblems: (1) provide counseling to partners about the materials and tools used to make dirty and rain water reservoirs, controltanks, and infiltration tanks; (2) providing counseling to partners about dirty and rain water collection tanks, control tanks, andinfiltration tanks; (3) provide training to partners making dirty and rain water reservoirs. The method used in counseling: lectures,discussions, and question and answer. The method used in the training: demonstration, question and answer, and discussion. Theresults of the activities: (1) partners have knowledge of the materials and tools used to make dirty and rain water storage tanks,control tanks, and infiltration tanks; (2) partners have knowledge of the functions of dirty and rain water collection tanks, controltanks and infiltration tanks; (3) partners have the skills to make dirty and rain water reservoirs, control tanks and infiltrationtanks, which also function as water conservation facilities.